The Problem of Historical Choice in East German Literature: Johannes Bobrowski in Context of the Postwar Literature of the 1950s-1970s - Salimzanova, Dilyara A.; Gilfanova, Gulnara T. (Journal of History Culture and Art Research, 2017)
The article tells about works of the famous German writer Johannes Bobrowski (1917-1965) born 100 years ago; the world literary community celebrates his 100 anniversary as in 2017. The poetic speech of Bobrowski, difficult for perception, reflected the main perspective of his poetry: history of the people and communication of the person with the nature. Art development of history, author’s cycle of stories and two novels of the original narrative technique in the conditions of totalitarian regime and continuous censorship, in many respects predetermined development of a genre of the historical novel in literature of the East German space of the "middle" of the last century. The creativity J. Bobrowski opens the new truth about the German life and history, thereby expanding a framework of art judgment of the past country.